2014
DOI: 10.1007/s11920-014-0538-9
|View full text |Cite
|
Sign up to set email alerts
|

Personality Disorders in Older Adults: Emerging Research Issues

Abstract: Empirical research focusing on personality disorders (PDs) among older adults is mainly limited to studies on psychometric properties of age-specific personality tests, the age neutrality of specific items/scales, and validation of personality inventories for older adults. We identified only two treatment studies-one on dialectical behavior therapy and one on schema therapy-both with promising results among older patients despite small and heterogeneous populations. More rigorous studies incorporating age-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 41 publications
0
49
0
3
Order By: Relevance
“…The past decades interest in research of PDs is growing both in adulthood and adolescence samples. However, psychometric research on PDs concerning older adults is still limited [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The past decades interest in research of PDs is growing both in adulthood and adolescence samples. However, psychometric research on PDs concerning older adults is still limited [1].…”
Section: Discussionmentioning
confidence: 99%
“…In geriatric medicine, older adults with multi-morbidity are treated for a variety of somatic, psychogeriatric, functional and social complaints. Research has shown that the presence of a personality disorder (PD) is a highly frequent complicating factor in both psychiatric and somatic health care [1]. The life style of patients with PDs, their lack of compliance, limited support system and conflicts with caregivers/professionals can complicate the treatment of somatic disorders in geriatric medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of personality disorders (PDs) in older adults is a highly underexplored topic (Van Alphen, Derksen, Sadavoy, & Rosowsky, 2012;Van Alphen et al, 2015). The number of publications on this subject is scant.…”
Section: Abstract Older Adults Personality Disorders Psychotherapymentioning
confidence: 99%
“…CBT has been proven efficacious for the treatment of depression and anxiety disorders (Gould, Coulson, & Howard, 2012a;2012b;Laidlaw & Thompson, 2014;Pinquart, Duberstein, & Lyness, 2007;Scogin & Shah, 2012) in older adults. Furthermore, case studies and empirical reviews indicate that cognitive behavioral therapy (CBT) and schema therapy (ST) are applicable for the treatment of PDs in later life (Bizzini, 1998;Dick & Gallagher-Thompson, 1995;James, 2003James, , 2008Van Alphen, 2010;Van Alphen et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation